Effects of ovariectomy on periodontal tissues following tooth replantation - Marão, Heloisa Fonseca [UNESP]; Mao, Jeremy J.; Casatti, Cláudio Aparecido [UNESP]; Coelho, Paulo G.; Ervolino, Edilson [UNESP]; Zhou, Jian; Silva, Vanessa Ferreira Da [UNESP]; Barioni, Sônia Regina Panzarini [UNESP] (Elsevier, 2016)
Objectives The aim of the study was to analyze the effects of ovariectomy on periodontal tissues following immediate tooth replantation by histomorphometric, immunohistochemistry, and μCT analysis. Materials and methods Eighty wistar rats (Rattus norvegicus albinos) with normal estrous cycles were randomly divided into two groups: ovariectomized (OVX) and Sham. Two months after surgery, the rats' upper right incisor was extracted followed by immediate reimplantation. The animals were sacrificed after 28, 45, and 60 days healing time. Histomorphometric and immunohistochemical analysis were performed by evaluation of PCNA and TRAP straining. Results The periodontal ligament was reinserted into the bone and cementum in the both groups. The immunohistochemical analysis revealed PCNA positive cells on the periodontal ligament in both groups at 28 days. Root resorption was noted at 45 days with immunoreactive cells for TRAP present in bone and tooth surface however no statistical differences between the groups were noticed. Histomorphometric analysis showed significant difference between groups in the periodontal ligament and root resorption parameters for the sub-items: intensity of chronic inflammatory infiltrate at 60 days (p < 0.01), the organization of the periodontal ligament at 28 days (p < 0.05), depth of root resorption at 45 days (p < 0.05) and at 60 days (p < 0.001). The μCT analysis showed multiple areas of bone resorption in association with OVX at 28 and 60 days with no significant differences between times in vivo. Conclusion The ovariectomy did not have significant influence in periodontal tissue parameters following tooth reimplantation.
Keywords: Immunohistochemistry; Micro-ct; Osteoclast; Ovariectomy; Tooth replantation